ENGLISH LANGUAGE AND HIGHER EDUCATION IN PAKISTAN: AN ANALYSIS OF POLICY MAKERS’ VIEWS - Irfan Ullah; Dr. Khalid Mahmood (International Journal of Contemporary Issues in Social Sciences, 2024)
Pakistan with a colonial past received English with official status because of this legacy at the time of inception in 1947. Pakistan as a federation of five provinces, has allowed official status for English language both at the national and provincial level. Policy making differences at the national and provincial level lead to problems at the confluence of policy and implementation, i.e. Higher Education Institutes in Pakistan. The paper collected and analysed views of the policy makers (through interviews) at the national and provincial levels, and manifestation of its effects on higher education. Analysis revealed that the socio-political dynamics and differences in linguistic and educational perspectives at the national and provincial levels created problems for a successful inclusive policy for English language in Pakistan.